Penerapan Lean Six Sigma untuk Meningkatkan Efisiensi Proses Inbound dan Outbound di Gudang PT XYZ - Amelia, Avril Firda; Moch. Tutuk Safirin (Jurnal Serambi Engineering, 2025)
The operational efficiency of the warehouse is a crucial factor in supporting the smooth running of the supply chain, especially in the inbound and outbound processes. The objective of this research is to analyse the root cause of the problem and reduce waste in the form of waiting time, which has a significant impact on the performance of PT XYZ's warehouse. This research applies the Lean Six Sigma approach, with tools in the form of Value Stream Mapping (VSM) to map the process flow, as well as the implementation of 5S as a proposed improvement to improve process order and work efficiency. The results showed that the high waiting time was caused by a lack of staff training, limited transport equipment, a continued reliance on manual processes and an inefficient warehouse layout. Suggested solutions included sorting goods by frequency of use, organising the warehouse layout, cleaning the warehouse regularly and developing clear SOPs. Implementation of the improvement recommendations resulted in a 51.38% increase in process cycle efficiency. This research shows that the Lean Six Sigma approach is effective in improving the efficiency of the warehouse process in a sustainable way.